PERANCANGAN MEDIA YOU ONLY LIVE ONCE (Y.O.L.O) SEBAGAI SARANA MENINGKATKAN MINAT BACA DAN TULIS BERBASIS WEB (STUDI KASUS FORUM LINGKAR PENA JAMBI): Reading, E-Book, You Only Live Once (YOLO), Writing - Aryanti, Dewi; -, Elzas (LP2M Universitas Nurdin Hamzah, 2017)
The condition of Indonesia's own interests read community is indeedquite a concern. Low interest read can be viewed from various aspects of one community's desire to buy a conventional printed book that feels quite damning. This is where the existence of E-books began tobe felt important, practical aspects and provide a viable alternative to conventional printed books substitute relatively less expensive. Reading itself is a process of improving vocabulary, command on the language and communication skills of a person. Someone who doesn't read will always experience the rarity of words when writing and speaking. On this occasion the author doing research on Flp Jambi Region as an organization with the goal of improving the kepenulisan reading and writing culture among the public by designing a media